Effects of temperature, salinity, and light on the growth performance, survival, final biomass, and digestive enzyme activities of juvenile Sipunculus nudus - Jianqiang Huang; Yongshan Liao; Ruzhuo Zhong; Chuangye Yang; Qingheng Wang; Yuewen Deng (Aquaculture Reports, 2023)
Enhancing the culture technology of Sipunculus nudus by improving the environmental conditions is a crucial means to address its scarcity. This study aimed to evaluate the effects of different environmental factors on the growth performance, survival, final biomass (FB), and digestive enzyme activity of juvenile S. nudus through three separate single-factor culture experiments. The period set for all experiments was 30 days. In the temperature experiment (five groups were set up: 15 °C, 20 °C, 25 °C, 30 °C, and 35 °C), juvenile S. nudus obtained high growth performance in the water temperature of 25–35 °C, but the survival rate (SR) of the 35 °C group was significantly lower than those of the 25 °C and 30 °C groups (P < 0.05). The optimal water temperature for the juvenile was 27.59 °C by fitting the regression equation using FB as the evaluation index. In the salinity experiment (five groups were set up: 15‰, 20‰, 25‰, 30‰, and 35‰), the juvenile S. nudus could obtain high growth performance and lipase activity in the salinity of 15–20‰ group, but the SR, protease activity, and amylase activity of 15‰ groups were significantly lower than those of the 20‰ groups (P < 0.05). By fitting the regression equation using FB as the evaluation index, the best salinity for juveniles was 19.93‰. In the light experiment (four groups were set up: natural light, semi-shade, light, and full-shade), the growth performance, FB, and lipase activity of the juveniles in the natural light group were significantly higher than those of the three other groups (P < 0.05), whereas the SR of the full-shade group was significantly lower than those of the three other groups (P < 0.05). This study provides a theoretical basis for exploring the suitable environmental conditions for the culture of S. nudus.